PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MOBIL MEREK TOYOTA (STUDI PADA KONSUMEN PT NASMOCO MAJAPAHIT, SEMARANG) - Prativi Putri Wulandari; Widayanto Widayanto (Universitas Diponegoro, 2020)
The automotive industry develops in line with the population growth. Tighter competition in the automotive world, especially cars, requires companies to make new innovations in order to continue to attract the attention of consumers so that they make purchase decisions. Toyota is a well-known car company that always holds the top position of car sales throughout Indonesia, including Semarang City. However, in 2015 - 2018 PT Nasmoco Majapahit, as one of the authorized Toyota dealers in Semarang City, could not meet the specified sales target. The result of the pre-survey about the considerations before buying Toyota at PT Nasmoco Majapahit shows that the most considered factor is promotion and service quality . This study aims to determine how the influence of promotion and service quality on purchasing decisions of Toyota car brand at PT Nasmoco Majapahit. The type of research used is explanatory research with the number of samples are 97 respondents. The sampling technique used is nonprobability sampling with a purposive sampling method and accidental sampling. Data collection using a questionnaire with a Likert measurement scale. Data were analyzed using IBM SPSS Statistics for Windows version 24. Based on the result of data analysis, there is a positive and significant influence between promotion and purchasing decisions. Service quality also has a positive and significant influence on purchasing decisions. The analysis also shows that the promotion and service quality simultaneously have a positive and significant effect on purchasing decisions. The author provides suggestions to PT Nasmoco Majapahit to increase promotions carried out in order to attract more buyers, maintain and continue to improve the quality of service both from the physical office and sales force so that buyers feel more comfortable and confident to purchase Toyota brand cars at PT Nasmoco Majapahit.